2013
DOI: 10.1007/s10637-013-9962-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small angiokinase inhibitor nintedanib (BIBF 1120) on QT interval in patients with previously untreated, advanced renal cell cancer in an open-label, phase II study

Abstract: Nintedanib administered at 200 mg twice daily was not associated with clinically relevant QT prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
7
45
0
Order By: Relevance
“…Nintedanib showed dose-proportional increases in C max and AUC over a dosage range of 50-450 mg once daily and 150-300 mg twice daily [52]. There was only slight accumulation of nintedanib following multiple twice-daily dosing [61], and interpatient variability for all pharmacokinetics parameters was moderate to high [51,52,61], in line with Phase I studies of other TKIs [62][63][64].…”
Section: Clinical Pharmacokineticssupporting
confidence: 74%
“…Nintedanib showed dose-proportional increases in C max and AUC over a dosage range of 50-450 mg once daily and 150-300 mg twice daily [52]. There was only slight accumulation of nintedanib following multiple twice-daily dosing [61], and interpatient variability for all pharmacokinetics parameters was moderate to high [51,52,61], in line with Phase I studies of other TKIs [62][63][64].…”
Section: Clinical Pharmacokineticssupporting
confidence: 74%
“…There was also no evidence of QT-prolongation with nintedanib treatment in INPULSIS or TOMORROW (pooled data; nintedanib: n = 723, placebo: n = 508). This finding is further supported by an oncology study of nintedanib in renal cell carcino ma patients ( n = 64), which also reported no evidence of clinically relevant QT-prolongation or drug-related cardiovascular events at a higher dose of 200 mg bid [34]. …”
Section: Nintedanib Use In Patients With Additional Risk Factorsmentioning
confidence: 67%
“…QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12. QTc prolongation was infrequent or absent with afatinib, crizotinib, ceritinib, dovitinib, imatinib, lapatinib, lenvatinib, nintedanib, pazopanib, and ponatinib 9, 14, 16, 17, 19, 24, 26, 27, 29, 30, 31, 32, 33, 35, 36, 38, 39, 72, 78, 81, 161, 162, 163, 164…”
Section: Resultsmentioning
confidence: 97%